Meta-Analisis: Validitas Penggunaan Media E-Booklet pada Pembelajaran Biologi - Ummi, Dara; Zulyusri, Zulyusri (Lembaga Yasin AlSys, 2025)
This research is motivated by the limited studies on the validity of e-booklets as a medium for biology learning, despite their potential to enhance students' understanding of complex material. The study aims to analyze the level of validity of e-booklets through a meta-analysis of ten articles published between 2021 and 2025, obtained from several accredited journals. The methodology employed is quantitative, utilizing descriptive analysis techniques across four aspects of validity: content, language, presentation, and graphics. Data were collected through document review and analyzed using the average percentage formula. The results indicate that e-booklets are classified as very valid, with an average validity score of 90.72%. This score comprises language (91.27%), content (91.19%), presentation (90.34%), and graphics (90.06%). These findings suggest that e-booklets meet the eligibility standards for effective and communicative biology learning media. This study concludes that e-booklets are suitable for use in biology education and contribute to the development of digital learning resources. The implications include strengthening the existing literature and providing practical recommendations for educators and media developers. Furthermore, this research paves the way for future studies on the effectiveness and practicality of e-booklets in broader educational contexts.